E-module for prevention of sexual harrasment in adolescent - Fira Ramli; Riska Ahmad; Yarmis Syukur (Fakultas Ilmu Pendidikan UNP)
Adolescence has a task to accomplish in order to accept the changes that occur. Encouragement achieves the full developmental task of mature sexual adolescence that comes from teenage interest and curiosity about sexuality. However, adolescents vent their curiosity to physical behavior that is part of sexual harassment. The high level of negative behavior toward sex this the attention of educators in preventing and overcoming them. Guidance and Counseling in schools has a preventive function, whereby Counselors can guide clients against self-harmful behavior with varied and flexible behaviors and techniques. Modules with high adaptability to the development of science and technology in the form of electronic module (e-module) can be a media service Counselor. E-module is a user manual in digital version that can be opened by using electronic device. The module may obtain Counselors in the form of services in a certain format.